Factor XIII immunoassay - Durda, Michael A; Kerlin, Bryce A; Waller, Amanda P; Wolfgang, Katelyn J (2025)
A method of detecting factor XIII activity in a biological sample is described. The method includes the steps of immobilizing or having obtained a capture antibody on a solid support, wherein the capture antibody comprises an antibody or antibody fragment that specifically binds to fibrinogen; incubating the biological sample with the capture antibody; contacting the immobilized capture antibody with α-thrombin, calcium, and α2-antiplasmin (AP); contacting the immobilized capture antibody with a detection antibody or antibody fragment that specifically binds to α2-AP, wherein the detection antibody or antibody fragment includes a detection label; and determining that factor XIII activity is present if the detection label is detected. The method can be used to diagnose a subject having factor XIII deficiency, or to monitor factor XIII levels in a subject undergoing factor XIII replacement therapy.